USING COMMUNICATIVE APPROACH TO TEACH VOCABULARY - Bosiyeva , Shahloxon Iqboljon qizi; Ergasheva, Gullola Odiljon Qizi; Khoshimova, Nargisa Abdullayevna (Educational Research in Universal Sciences, 2023)
The purpose of this thesis is to explore and evaluate the using communicative approach to teach vocabulary in the English language teaching.This thesis is about playing techniques as a way of increasing lexical skills in the primary stages of teaching English. The information given in this thesis will be of value to anyone occupied in teaching English language; to anyone interested in methods of teaching foreign language; to anyone interested in playing techniques and how to use them during the lessons correctly; to anyone who has problems with memorizing new words, group of words and phrases.